PENINGKATAN STATUS GIZI BALITA MELALUI PENYAJIAN MENU MAKANAN SECARA VARIATIF - Sri Untari; Dhiyan Nany Wigati; Meity Mulya Susanti; Ruli Mawarista Kori (LPPM AN Nuur, 2024)
Background: Toddlers are a vulnerable age group where the problem of underweight in toddlers can have a serious impact on the level of health and quality of life of toddlers in the following period. Lack of knowledge about nutrition has an impact on the mother's low ability and awareness in choosing types of food and providing appropriate food variations. with the needs of toddlers. Method: This activity was carried out to find solutions to problem solving through village community deliberations and then health education about balanced nutritional menus toddler and prepaing varied menus. Results: After carrying out health education about balanced nutrition and preparing varied menus, there was an increase in knowledge among mothers of toddlers and they were able to prepare varied menus. Conclusion: Parents' knowledge about balanced menus increases, they are able to prepare menus in a varied manner so that it is hoped that they can improve the nutritional status of toddlers.